Pengaruh Biaya Lingkungan dan Corporate Social Responsibility Terhadap Kinerja Keuangan - Ayu Lestari Tambunan; Mentari Dwi Aristi; Zul Azmi (Jurnal Wira Ekonomi Mikroskil, 2023)
This study aims to identify the effect of environmental costs and corporate social responsibility on financial performance over the 2016-2020 period. A quantitative research approach is applied to objects of observation in the mining sector listed on the Indonesia Stock Exchange, with a total sample of 40 which can be accessed via www.idx.co.id. With the technique of testing data multiple regression test hypothesis testing is carried out. The results of the study show that financial performance is affected by environmental costs in the mining sector in 2016-2020, while corporate social responsibility has no significant effect on financial performance in the mining sector in 2016-2020.